155k views
4 votes
Explicit formula for the sequence -3,-14,-25,-36

2 Answers

6 votes

Answer:

aₙ = aₙ₋₁ -11

Explanation:

We have given the sequence:

-3,-14,-25,-36

We have to find the explicit formula.

The first term in this sequence is:

a₁ = -3

The common difference is:

a₂-a₁= -14-(-3) = -11

a₃-a₂ = -25-(-14) = -11

a₄-a₃ = -36-(-25)= -11

Common difference d = -11

The general formula is :

aₙ = aₙ₋₁ +d

Here d = -11 so,

aₙ = aₙ₋₁ -11 is the explicit formula.

User Vikas Dwivedi
by
5.5k points
3 votes

ANSWER


a_(n)=a_(n-1) - 11 \: \: ,a_1 = - 3

EXPLANATION

The given sequence is


-3,-14,-25,-36,...

The first term of the sequence is


a_1=-3

The common difference is


d = - 14 - - 3


d = - 11

The recursive formula is


a_(n)=a_(n-1) - 11 \: \: ,a_1 = - 3

User Kkpoon
by
5.0k points